Prospective motion correction improves high‐resolution quantitative susceptibility mapping at 7T. Issue 3 (9th October 2018) - Mattern, Hendrik; Sciarra, Alessandro; Lüsebrink, Falk; Acosta‐Cabronero, Julio; Speck, Oliver
Abstract : Purpose: Recent literature has shown the potential of high‐resolution quantitative susceptibility mapping (QSM) with ultra‐high field MRI for imaging the anatomy, the vasculature, and investigating their magnetostatic properties. Higher spatial resolutions, however, translate to longer scans resulting, therefore, in higher vulnerability to, and likelihood of, subject movement. We propose a gradient‐recalled echo sequence with prospective motion correction (PMC) to address such limitation. Methods: Data from 4 subjects were acquired at 7T. The effect of small and large motion on QSM with and without PMC was assessed qualitatively and quantitatively. Full brain QSM and QSM‐based venograms with up to 0.33 mm isotropic voxel size were reconstructed. Results: With PMC, motion artifacts in QSM and QSM‐based venograms were largely eliminated, enabling—in both large‐ and small‐amplitude motion regimes—accurate depiction of the cortex, vasculature, and other small anatomical structures that are often blurred as a result of head movement or indiscernible at lower image resolutions. Quantitative analyses demonstrated that uncorrected motion could bias regional susceptibility distributions, a trend that was greatly reduced with PMC. Conclusion: Qualitatively, PMC prevented image degradation because of motion artifacts, providing highly detailed QSM images and venograms. Quantitatively, PMC increased the reproducibility of susceptibility measures.